The Effect of Estrogen in the Prevention of Adhesion Reformation After Hysteroscopic Adhesiolysis: A Prospective Randomized Control Trial. Issue 8 (August 2022) - Yang, Lingling; Ma, Ning; Song, Dongmei; Huang, Xiaowu; Zhou, Qiaoyun; Guo, Yan; Xia, Enlan; Shi, Xiaoyu; Li, Tin Chiu
Abstract : (Abstracted from J Minim Invasive Gynecol 2022;29:871–878) Asherman syndrome occurs when intrauterine adhesions (IUAs) are produced after trauma to the basalis layer of the endometrium (often following endometrial curettage in the gravid uterus). The syndrome may present in affected women as changes in menstruation including secondary amenorrhea, oligomenorrhea, dysmenorrhea, infertility, or recurrent miscarriage.